The Acute Readiness Monitoring Scale: Assessing Predictive and Concurrent Validation - Summers, Simon J.; Keegan, Richard J.; Flood, Andrew; Martin, Kristy; McKune, Andrew; Rattray, Ben (Frontiers in Psychology, 2021)
To complement and enhance readiness-monitoring capability, the Acute Readiness Monitoring Scale (ARMS) was developed: a widely applicable, simple psychometric measure of perceived readiness. While this tool may have widespread utility in sport and military settings, it remains unknown if the ARMS demonstrates predictive and concurrent validity. Here, we investigated whether the ARMS is: 1) responsive to an acute manipulation of readiness using sleep deprivation, 2) relates to biological markers of readiness (cortisol/heart-rate variability [HRV]), and 3) predicts performance on a cognitive task. Thirty young adults (aged 23 ± 4 years; 18 females) participated. All participants engaged in a 24-hour sleep deprivation protocol. Participants completed the ARMS, biological measures of readiness (salivary cortisol, HRV), and cognitive performance measures (psychomotor vigilance task) before, immediately after, 24-, and 48-hours post sleep deprivation. All six of the ARMS subscales changed in response to sleep deprivation: scores on each subscale worsened (indicating reductions in perceived readiness) immediately after sleep deprivation, returning to baseline 24/48 hours post. Lower perceived readiness was associated with reduced awakening responses in cortisol and predicted worse cognitive performance (slower reaction time). No relationship was observed between the ARMS and HRV, nor between any biological markers of readiness (cortisol/HRV) and cognitive performance. These data suggest that the ARMS may hold practical utility in detecting, or screening for, the wide range of deleterious effects caused by sleep deprivation; may constitute a quick, cheap and easily interpreted alternative to biological measures of readiness; and may be used to monitor or mitigate potential underperformance on tasks requiring attention and vigilance.